Endocrine stress response in pregnancy and 12 weeks postpartum – Exploring risk factors for postpartum depression. (March 2021) - Stickel, S.; Eickhoff, S.B.; Habel, U.; Stickeler, E.; Goecke, T.W.; Lang, J.; Chechko, N.
Abstract: Pregnancy and the postpartum period are characterized by physiological alterations in cortisol and cortisone levels. In the present study, we sought to explore the risk factors for postpartum depression (PPD) and self-remitting postpartum adjustment disorder (AD) and whether cortisol/cortisone metabolism might have any bearing on them. Hair samples from 196 participants (mean age = 31.44, SD = 4.71) were collected at two time points (1–6 days after childbirth and 12 weeks postpartum) to determine the cumulative hair cortisol (HCC) and hair cortisone (HCNC) exposure in the third trimester and during the 12 weeks postpartum. Compared to the non-depressed group (ND, n = 141), more women in the AD (n = 28) and PPD (n = 27) groups had a personal or family history of depression and more stressful life events. Compared to ND and PPD, more women in the AD group had birth-related complications with their children being more often transferred to a pediatric ward. The factors associated with PPD were found to include being unmarried and having a lower household income, less support at home, more subjectively perceived stress after childbirth and lower maternal sensitivity. The natural decrease in HCC concentration from the third trimester to 12 weeks postpartum was significant only in the ND and AD groups, but not in PPD. In summary, prolonged subjectively perceived postpartum stress associated with living situations may contribute to the development of PPD while birth- and child-related complications are likely to trigger brief episodes of AD. Only in ND and AD, the pregnancy-related physiological changes in glucocorticoid levels return to the pre-pregnancy baseline after 12 weeks. Our observations point to the difference between the ND and PPD groups in glucocorticoid metabolism-related postpartum adjustment, which may be a factor in the development of PPD. Highlights: Pregnancy and the postpartum period are marked by changes in cortisol concentration. Pregnant and postpartum women might be susceptible to postpartum depression (PPD). Pregnant women have the same endocrine levels irrespective of whether or not they developed PPD. Physiological changes in the HPA axis activity do not normalize in women with PPD. Postpartum depression is linked to postpartum stress and living situations.